The perception of mental health of older people participating in a community socialization group (Research, Society and Development, 2023)
Objective: To analyze the perception of mental health of elderly people who participate in a living group. Method: Descriptive, exploratory, study with a qualitative approach. The study was conducted with six elderly participants to the Community Group of a Basic Health Unit of a municipality in southeastern Goiás. Data were collected through the application of the Beck Depression Index, the Rosenberg Self-Esteem Scale, and an interview with a semi-structured script, analyzed through Bardin's Content Analysis. During the Corona Virus Disease pandemic, the interviews were conducted in order to respect the safety protocols established by the Ministry of Health, such as the use of an N95 mask and the use of 70% alcohol gel on the hands, and with the full doses of the vaccine. Results: 66.7% of the elderly had some symptoms of depression and all had reasonable self-esteem. The qualitative analyzes were subdivided into the following categories: “The feeling of sadness and emotions perceived by the elderly in difficult moments and in limiting situations of life”, “Strategies for dealing with situations that trigger feeling of sadness” and “Importance of the Coexistence Group in the pandemic period and in the social life of the elderly”. Final considerations: Family issues, death of loved ones, disabilities and inactivity have a negative impact on mental health, causing sadness and a sense of abandonment. The coexistence group is among the coping strategies for maintaining mental health, enabling active aging and social support.